Supervisi Kepala Sekolah Terhadap Guru di SMK LPMD Adow Kecamatan Pinolosian Tengah Kabupaten Bolaang Mongondow Selatan - Muliadi Mokodompit (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2021)
Principal's supervision is part of efforts to ensure the quality of academic activities. Through the supervision the principal can direct teachers to improve the quality of learning in schools. This study aims to: